Dipyrone attenuates cerebral vasospasm after experimental subarachnoid hemorrhage in rabbits - Silav, Gökalp; Ergün, Hakan; Dolgun, Habibullah; Sancak, Tanzer; Sargon, Mustafa Fevzi; Egemen, Nihat (Edizioni Minerva Medica, 2017)
BACKGROUND: The purpose of this study was to evaluate the effect of the systemic administration of dipyrone in a triple subarachnoid hemorrhage (SAH) model of cerebral vasospasm in rabbits. METHODS: Experimental subarachnoid hemorrhage was induced in rabbits by injecting autologous arterial blood into the cisterna magna. Digital subtraction angiographies (DSA) were performed before and after the first experimental SAH, and at 30, 45, 60 minutes and 72 hours after the first drug administration to measure the diameter of basilar artery. Intracisternal blood injections were repeated 24 and 48 hours after the first injection. Dipyrone (N.= 20) or 0.9% NaCl (N.= 20) was administered intravenously after initial SAH induction and repeated at 8-hour intervals intramuscularly. After sacrificing by perfusion-fixation, basilar arteries were removed and sectioned for transmission electron microscopic (TEM) examination. RESULTS: The average basilar artery diameter measured by DSA was 724 +/- 19 mu m in the control, and 686 +/- 29 mu m in treatment group before SAH. After SAH, mean basilar artery diameters decreased to 71% and 68% of their basal values, respectively. Dipyrone significantly attenuated the basilar artery diameter at one and 72 hours after the first drug administration, in comparison to the control group. TEM studies showed more edema in the endothelial cells of the basilar arteries of the control group when compared to the treatment group. CONCLUSIONS: Dipyrone showed a beneficial effect in autologous blood-induced basilar artery vasospasm in rabbits. These data support the idea that dipyrone can be a potential candidate drug to be tested in patients suffering from cerebral vasospasm secondary to subarachnoid hemorrhage.
WOS: 000410533100004
PubMed ID: 25366581
Keywords: Basilar artery; Intercranial Vasospasm; Dipyrone; Rabbits